A Rare Case of Sclerosing Encapsulating Peritonitis Secondary To Tuberculosis - Nirupam Konwar Baishya (National Scientific Medical Center, 2024)
Sclerosing encapsulating peritonitis is a relatively rare, potentially life-threatening condition that causes intestinal loops to become encapsulated as a fibro-collagen cocoon. Despite advances in treatment, mortality is high. It shows vague clinical signs and is therefore difficult to diagnose clinically. Abdominal Contrast Enhanced CT (CECT) is an excellent modality for diagnosing the condition, assessing its complications such as perforation, and guiding the treatment approach to the condition. This case report highlights a rare case of sclerosing encapsulating peritonitis in a young adult secondary to tuberculosis. Although the most common secondary cause of SPE is peritoneal dialysis, consideration of tuberculosis as a cause of such a condition is very important, especially in the Indian context.